Analytical study of third-mode lateral thermal buckling for unburied subsea pipelines with sleeper. (1st August 2018) - Wang, Zhenkui; van der Heijden, G.H.M.; Tang, Yougang
Highlights: A mathematical model is developed for a pipeline with sleeper as buckle initiator. An energy analysis reveals a critical temperature for imperfection-driven buckling. Third-mode buckling takes lower energy than first-mode buckling, so is more likely. The effect of sleeper height and sleeper friction on lateral buckling is studied. Critical temperature can be decreased by increasing height or decreasing friction. Abstract: Unburied subsea pipelines operating under high-temperature and high-pressure conditions tend to relieve their axial compressive force by forming lateral buckles. In order to manage lateral buckling, a sleeper is often employed as a buckle-initiation technique to ensure pipeline integrity. In this study, analytical solutions of third-mode lateral buckling for unburied subsea pipelines with sleeper are derived. The analytical solution is compared with experimental data in the literature and shows good agreement. The stability of the buckled pipeline is investigated by means of an energy analysis and it is found that third-mode lateral buckling has lower energy than first-mode buckling, which means that third-mode buckling is more likely to happen in practice. The influence of sleeper height and sleeper friction on lateral post-buckling behaviour is illustrated and analysed, with particular attention paid to the minimum critical temperature difference, lateral displacement amplitude and maximum stress. Our results show that increasing the height of the sleeper or decreasing the friction between pipeline and sleeper can both be used to decrease the minimum critical temperature difference, but their influence on the maximum stress is opposite.